FAKTOR TEMAN SEBAYA DALAM MEMPENGARUHI MINAT MAHASISWA MEMILIH JURUSAN PENDIDIKAN MATEMATIKA DI IAIN PADANGSIDIMPUAN - Rama Nida Siregar; Sufyani Prabawanto; Suparni Suparni; Abdul Mujib (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Peers have an influence on the development of adolescents, especially prospective students, especially when choosing a major in a college. Choosing a major in a college for each prospective student is often related to the peer group. Some prospective students in Indonesia when choosing a major are still influenced by peers when making a decision, this cannot be separated from the role of peers as people who have more or less in common in age and school who can broaden their views and influence the social development of adolescents, especially when a teenager will decide something regarding his education and career in the future. This study aims to describe the peer factor in influencing student interest in choosing a major in mathematics education. This research was conducted at IAIN Padangsidimpuan and the research participants were 25 students of the tadris/mathematics education study program at IAIN Padangsidimpuan. This research uses quantitative and qualitative approaches with descriptive research and percentage analysis techniques. In this study, the data obtained are data derived from questionnaires that have been filled out by research respondents. While the data analysis technique used in this study is statistical analysis of percentages, because the purpose of this study is to provide a description of the existing data. The results of peer factor analysis are divided into five categories in influencing student interest in choosing mathematics education majors, namely: a) very high influence 24%, b) high influence 40%, c) moderate influence 20%, d) low influence 12%, and e ) has a very low effect of 4%.